Cognition and incident coronary heart disease in late midlife: The Whitehall II study - Singh-Manoux, Archana (2009)
The purpose of this study was to investigate whether cognitive function in midlife predicts incident coronary heart disease (CHD), followed up over 6 years. Data on 5292 (28% women, mean age 55) individuals free from CHD at baseline were drawn from the British Whitehall II study. We used Cox regression to model the association between cognition and CHD in analyses adjusted for socio-demographic variables, cardiovascular risk factors and health behaviors. The results show a one standard deviation lower score on the “general” cognitive measure and measures of reasoning and vocabulary to be associated with elevated CHD risk. There was some evidence that these effects differed between high and low socioeconomic status (SES) groups with associations only seen in the low SES group. These results were not explained by threshold effects or by the different SES groups representing different parts of the cognitive test score distribution. Three other possible explanations of these results are discussed: sub clinical vascular disease drives the observed association but no effect is observed in the high SES group due to compensation provided by greater cognitive reserve, cognition is a marker of overall bodily integrity particularly in low-SES groups, and SES is a moderator of the association between cognition and CHD, because it marks a range of other risk factors.